Analisis Sistem Manajemen Kinerja pada Varna Culture Hotel Surabaya - Gisti Riza Adistie; Maulida Hirdianti Bandi (Akuntansi : Jurnal Akuntansi Integratif, 2020)
This research is to design performance measurement using the Balanced Scorecard method and to find out how much influence the performance measurement tools for the company. The design of the Balanced Scorecard method is based on four perspectives, namely financial perspective, customer perspective, internal business process perspective, and growth and learning perspective. This research is a qualitative exploratory study, because it requires research with in- depth interviews to obtain information about the performance management system that is implemented at the Varna Culture Hotel. The results of this study indicate that the performance measurement tool with the Balanced Scorecard method is basically a translation of the strategy and objectives to be achieved by the company in the long run, which is then measured and monitored on an ongoing basis. Therefore the Balanced Scorecard method is not only a translation of the strategy, but has become an important part in determining strategy and assisting the management of Varna Hotels in making decisions.